Wine trails of Irig municipality: Perspectives of development - Vujko, Aleksandra; Gajić, Tamara; Gudurić, Ivana (Hotel and Tourism Management, 2017)
Our vineyards, the wine of superior quality, equipped cellars, wine salami, authentic wine houses, excellent cuisine and courtesy winemakers, tourism workers and indigenous peoples are the main motivation for the development of wine tourism. Regarding the methodological basis, the object of this work comprises the current state of wine tourism in the Municipality of Irig, the formation of the wine trail, possible association of winemakers, monitoring and analysis of the results achieved, the preservation of tradition through wine tourism, promotion of gastronomy, the promotion of wine, viticulture and enology, but also constantly adapting refined delicious increasingly demanding tourism demand. The aim of the paper is to focus on improving the overall image of tourism in the positioning of wine tourism, which would to some extent prolong the duration of the tourist season, and the achievement of positive economic effects suitable for the development of both individual wine producers, as well as the entire Irig municipality. Methods that have been used when writing the paper are in the form of field research observation and interviews with the owners of wine cellars and wineries, and questionnaire surveys as well. The survey was conducted among residents of the Municipality of Irig in order to get the most relevant statistical processing of the data that will be used for understanding the present, and predict the future state of the development of wine tourism.